Prevalência de anticorpos anti-Leptospira spp. e aspectos epidemiológicos da infecção em bovinos do estado de Goiás - MARQUES, Alberto Elias (2008)
The state of Goias has the third largest cattle herd in Brazil, but the production has some obstacles, such as reproductive diseases, which cause abortions and infertility, including leptospirosis, also important in public health. This study aimed to determine the prevalence of antibodies against Leptospira spp., determine their regional distribution and evaluate the main risk factors for the disease in cattle in the State of Goias. The study was conducted using the 4571 samples taken from 715 properties of 213 of the 246 municipalities in the state of Goiás The samples were analysed by the microagglutination test. To determine the correlation between the prevalence and associated factors, the test of Logistic Regression was used through the software SPSS. The percentage of positive samples for at least one of the16 serovars tested was 62.2%, with major prevalence of co-agglutination (40.24%), followed by serovars wolffi (14.53%), hardjo (12.70 %), grippotyphosa (10.55%) and shermani (6.55%). The prevalence of antibodies against Leptospira spp. proved to be associated to the following factors: stratum of production, with a greater prevalence in stractum one, predominantly for meat production; practice of artificial insemination; cattle breed; presence of sheep and goats; presence of capybaras; purchase of cattle in breeding exhibitions and from other properties; rent of pastures in any time of year; presence of maternity paddock and occurrence of abortions. On the other hand, it was not found correlation with the following factors: type of exploitation and creation charged in the property; kind of milking; presence of horses, pigs, dogs, cats, deer and other wild animals; presence of other animals; purchase of animal at fairs and/or auctions; selling of cattle in exhibitions, in fairs and/or auctions, from traders or from other properties; presence of pastures in common with other properties, veterinary care and vaccination against brucellosis, IBR and BVD. It was concluded that leptospiral infection is endemic in Goias.